2010
DOI: 10.7150/ijbs.6.834
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Bioconversion Production of D-xylitol and Its Detection and Application

Abstract: D-Xylitol is found in low content as a natural constituent of many fruits and vegetables. It is a five-carbon sugar polyol and has been used as a food additive and sweetening agent to replace sucrose, especially for non-insulin dependent diabetics. It has multiple beneficial health effects, such as the prevention of dental caries, and acute otitis media. In industry, it has been produced by chemical reduction of D-xylose mainly from photosynthetic biomass hydrolysates. As an alternative method of chemical redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 83 publications
0
43
0
5
Order By: Relevance
“…In addition, studies have shown that xylitol prevents osteoporosis, haemolytic anaemia and acute otitis (Mussatto and Roberto 2002). Xylitol can be produced by the chemical reduction of D-xylose derived mainly from lignocellulose biomass hydrolysates (Chen et al 2010;da Silva and Chandel 2012;Mohamad et al 2015). However, the requirement for several purification steps to separate xylitol from other polyols and sugars during the chemical process increases the production cost.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, studies have shown that xylitol prevents osteoporosis, haemolytic anaemia and acute otitis (Mussatto and Roberto 2002). Xylitol can be produced by the chemical reduction of D-xylose derived mainly from lignocellulose biomass hydrolysates (Chen et al 2010;da Silva and Chandel 2012;Mohamad et al 2015). However, the requirement for several purification steps to separate xylitol from other polyols and sugars during the chemical process increases the production cost.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, the production of secondgeneration bioethanol has allowed the use of these biomasses in its production, which guarantees high selectivity of the product, low cost and safety (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rare sugar derivatives are used as effective antivirals, for example against hepatitis-B virus and human immunodeficiency virus, and antitumor agents [7, 8]. The demand for rare sugars has been rising recently; global production was in excess of 133 million tons in 2002.…”
Section: Introductionmentioning
confidence: 99%